PENGARUH UKURAN PERUSAHAAN, FINANCIAL LEVERAGE DAN LABA SEBELUM PAJAK TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN (STUDI EMPIRIS PADA PERUSAHAAN MANFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2018) - Yulia Fitri; Firzatullah Firzatullah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The goals of this examination are (1) to break down the impact of organization size on the decision of stock bookkeeping strategies, (2) to dissect the impact of monetary influence on the decision of inventory accounting methods (3) to investigate the impact of benefit before charge on the decision of inventory accounting methods (4) to examine the impact of size organization, monetary influence and benefit before charge on the determination of inventory accounting methods. This exploration is an experimental investigation led on assembling organizations recorded on the Indonesian stock trade during 2015-2018 and there are 78 organizat